Electrochemical dissolution behavior of 07Cr16Ni6 alloy in sodium nitrate solution - Jingtao Wang; Zhaoyang Zhang; Wei Xue; Hao Zhu; Kun Xu; Yang Liu (Arabian Journal of Chemistry, 2024)
07Cr16Ni6 alloy is a kind of martensitic-austenitic duplex stainless steel that is widely used in aviation and aerospace. Electrochemical machining (ECM) is an ideal manufacturing process for 07Cr16Ni6 alloy because of its high machining accuracy and good final surface quality. Studying the electrochemical dissolution behavior is pre-requisite and key to optimizing the ECM process; however, few studies have focused on the electrochemical dissolution behavior of 07Cr16Ni6 alloy. In this work, the corrosion behavior, passivation characteristics, efficiency curves, and material-removal process of 07Cr16Ni6 alloy in NaNO3 solution were comprehensively investigated. Based on the curves of potentiodynamic polarization and conductivity curve, it was found that both of them have significant passive and transpassive characteristics. The results of X-ray photoelectron spectroscopy and electrochemical impedance spectroscopy indicated that the passive film was mainly composed of Fe3O4, α-Fe2O3, γ-Fe2O3, Cr2O3, NiO, SiO, and SiO2, and its structure was composed of a dense inner-layer film and a loose outer-layer film. A schematic model was proposed to characterize the interface structure between the 07Cr16Ni6 alloy, the passive film and electrolyte. ECM tests were performed at different current densities and for different corrosion times. The current-efficiency results indicate that the material-removal rate can be divided into three regions. The current efficiency first rises gently, then rises steeply once the current density exceeds 26 A cm−2; it finally remains stable at current densities greater than 45 A cm−2. The corrosion morphology exhibits loose, blocky bulges at low current density, while the surface exhibits lath-type martensite structures when the current density j > 15 A cm−2. The material-dissolution process of the 07Cr16Ni6 alloy in NaNO3 solution at 20 A cm−2 was presented. Finally, a model of dissolution was established to characterize the electrochemical dissolution of the 07Cr16Ni6 alloy in NaNO3 solution.